1991
DOI: 10.1063/1.460454
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of adsorbed Mo(CO)6 induced by direct photoexcitation and hot electron attachment. II. Physical mechanisms

Abstract: Articles you may be interested inPlasmon-induced photoexcitation of "hot" electrons and "hot" holes in amorphous silicon photosensitive devices containing silver nanoparticles The wavelength dependence of photoinduced hot electron dissociative attachment to methyl bromide adsorbed on gallium arsenide (110) Photodissociation of adsorbed Mo(CO)6 induced by direct photoexcitation and hot electron attachment. I. Surface chemistryPhotodissociation of Mo (CO) 6 adsorbed on potassium-free and potassium-preadsorbed Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 122 publications
1
15
0
Order By: Relevance
“…The authors of that work identified the HOMO→LUMO transition as mechanism which leads to subsequent decomposition of the molecule. 23 Since the photon energy is similar to the deposition threshold energy of the electrons in our experiments we conclude that the same dissociation mechanism is effective if Mo͑CO͒ 6 is dissociated locally by electrons from the STM tip. As soon as the electrons arrive at the physisorbed layer with approximately double ͑triple, etc.͒ the energy necessary for excitation of Mo͑CO͒ 6 , one electron can induce two ͑three, etc.͒ dissociation events.…”
Section: Growth Mechanismsupporting
confidence: 66%
See 1 more Smart Citation
“…The authors of that work identified the HOMO→LUMO transition as mechanism which leads to subsequent decomposition of the molecule. 23 Since the photon energy is similar to the deposition threshold energy of the electrons in our experiments we conclude that the same dissociation mechanism is effective if Mo͑CO͒ 6 is dissociated locally by electrons from the STM tip. As soon as the electrons arrive at the physisorbed layer with approximately double ͑triple, etc.͒ the energy necessary for excitation of Mo͑CO͒ 6 , one electron can induce two ͑three, etc.͒ dissociation events.…”
Section: Growth Mechanismsupporting
confidence: 66%
“…5. 23 For Mo͑CO͒ 6 physisorbed on Si(111)-(7ϫ7), the highest occupied molecular orbital ͑HOMO͒ (4d) and the lowest unoccupied molecular orbital ͑LUMO͒ (4d*) are 7 and 3.2 eV, respectively, below the vacuum level. Dissociation of Mo͑CO͒ 6 can be induced by excitation of an electron from the HOMO to the LUMO.…”
Section: Growth Mechanismmentioning
confidence: 96%
“…Ho and co-workers 37,56,57 demonstrated that direct excitation plays a major role in photodissociation of Mo͑CO͒ 6 physisorbed on various substrates above 250 nm. The direct excitation in the photochemistry of weakly adsorbed Mo͑CO͒ 6 on various surfaces was confirmed from the close resemblance of the wavelength dependence of the photodissociation yield to that of optical absorption measured in cyclohexane.…”
Section: Comparison With Other Systemsmentioning
confidence: 99%
“…In their results, SSB was observed as low as at 3-eV incident-electron energy. Since this report, Sanche and other researchers [3][4][5][6][7][8][9] has pioneered the investigation of DNA damage induced by LEE irradiation and explained the observation of DNA damage with dissociative electron attachment (DEA) process. DEA occurs when a free unbound electron attaches to a molecule to form a temporary negative ion, then dissociates into a negative ion and a neutral fragment [3,4]:…”
Section: Introductionmentioning
confidence: 99%